Método para priorização de programas de melhoria contínua em um ambiente de máquina única: proposta e aplicação - Barco, Clarissa Fullin (Universidade Federal de São Carlos, 2013)
Companies have been considering the responsiveness as a competitive criterion, trying to meet current market that requires simultaneously quality, efficiency, punctuality and customization. So, the lead time reduction becomes a strategic issue for the manufacturing management, considering that improvement programs on lead time reduction have been widely approached by Lean Manufacturing and Quick Response Manufacturing. Studies on improvements on shop floor parameters in order to reduce the lead time were addressed in numerous studies, such as the work of Godinho Filho and Uzsoy (2008a). Due to resource constraints existing in practice, there is a need to investigate which variable can be prioritized in the development of improvement projects, due to their potential for reducing the lead time. Therefore, this study aims to address this gap in the literature and from the business, expanding Godinho Filho and Uzsoy (2008a) work and proposing a method for selecting improvement programs aimed at reducing the lead time. To achieve this goal, we conducted a literature review, a case study on a company of the aviation industry, as well as simulations using a model created from the System Dynamics approach and Factory Physics. In addition to outlining the research question of this work, the case study aims to present to the reader an application of the method proposed. Thus, for the environment studied, i.e. a bottleneck single machine of a machining process, the result of applying the seven steps of the method was the potential improvement of 84.63% on lead time, which can be obtained with a design 1373% improvement in mean time between failures, requiring an effort of 5880 h. As an alternative to the company, a 34.76% reduction in lead time would also be possible through the investment of 1960h working for an improvement of 72% in the coefficient of variation of the repair time.
Keywords: Planejamento da produção; Variáveis de chão-de-fábrica; Lead time; Shop floor parameters; Factory physics; System dynamics; Redução de lead time; Factory physics; Dinâmica de sistemas; ENGENHARIAS::ENGENHARIA DE PRODUCAO